Long-term treatment outcome of patients with complete bilateral cleft lip and palate: a retrospective cohort study - Yoshitsugu Hattori; Betty C. J. Pai; Takafumi Saito; Pang‐Yun Chou; Ting-Chen Lu; Chun‐Shin Chang; Yu-Ray Chen; Lun‐Jou Lo (2023)
Background: Patients with cleft lip and palate have functional and esthetic impairment and typically require multiple interventions in their life. Long-term evaluation following a treatment protocol, especially for patients with complete bilateral cleft lip and palate (BCLP), is important but was rarely reported in the literature. Patients and methods: A retrospective review was conducted on all patients with complete BCLP born between 1995 and 2002 and treated at our center. Inclusion criteria were having adequate medical records and receiving continuous multidisciplinary team care at least until 20 years of age. Exclusion criteria were lack of regular follow-up and congenital syndromic abnormalities. The medical records and photos were reviewed, and facial bone development was evaluated using cephalometric analysis. Results: A total of 122 patients were included, with a mean age of 22.1 years at the final evaluation in this study. Primary one-stage cheiloplasty was performed in 91.0% of the patients, and 9.0% underwent two-stage repair with an initial adhesion cheiloplasty. All patients underwent two-flap palatoplasty at an average of 12.3 months. Surgical intervention for velopharyngeal insufficiency was required in 59.0% of patients. Revisional lip/nose surgery was performed in 31.1% during growing age and in 64.8% after skeletal maturity. Orthognathic surgery was applied in 60.7% of patients with retruded midface, of which 97.3% underwent two-jaw surgery. The average number of operations to complete the treatment was 5.9 per patient. Conclusion: Patients with complete BCLP remain the most challenging group to treat among the cleft. This review revealed certain suboptimal results, and modifications have been made to the treatment protocol. Longitudinal follow-up and periodic assessment help to establish an ideal therapeutic strategy and improve overall cleft care.